2015
DOI: 10.1590/1678-457x.6449
|View full text |Cite
|
Sign up to set email alerts
|

Glycemic index and glycemic load of tropical fruits and the potential risk for chronic diseases

Abstract: The objective was to determine the glycemic index and glycemic load of tropical fruits and the potential risk for chronic diseases. Nine fruits were investigated: coconut water (for the purpose of this study, coconut water was classified as a "fruit"), guava, tamarind, passion fruit, custard apple, hog plum, cashew, sapodilla, and soursop. The GI and GL were determined according to the Food and Agriculture Drganization protocol. The GL was calculated taking into consideration intake recommendation guidelines; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 28 publications
2
20
0
3
Order By: Relevance
“…Also the hypoglycemic activity of A.muricata leaves might be attributed to the presence of certain flavonoids that have the ability to inhibit α-glucosidase (Rahmiet al, 2016) thus decreasing carbohydrate metabolism and glucose absorption (Hardokoet al, 2015). Additionally, the glycemic index and the glycemic load of A.muricata were found to be low in A. muricata, which supports its hypoglycemic potential (Passos et al, 2015).…”
Section: Discussionmentioning
confidence: 75%
“…Also the hypoglycemic activity of A.muricata leaves might be attributed to the presence of certain flavonoids that have the ability to inhibit α-glucosidase (Rahmiet al, 2016) thus decreasing carbohydrate metabolism and glucose absorption (Hardokoet al, 2015). Additionally, the glycemic index and the glycemic load of A.muricata were found to be low in A. muricata, which supports its hypoglycemic potential (Passos et al, 2015).…”
Section: Discussionmentioning
confidence: 75%
“…Also it is understood that different complex carbohydrates could have different physiological effects. Foods with high GI are reported to have a deleterious effect on health and therefore should be avoided [1,23].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is important that the GI of our fruits and vegetables be determined to better guide the choices of the consumer. It was reported that the GI values of the same type of fruits cultivated in different geographical location may vary and could be due to the environmental conditions or difference in sugar composition, fiber content, stage of ripening, acid content, presence of anti nutrients, method of storage and harvesting or it could be the methods used to determine the GI of the test foods [22][23][24][25]. This study investigated the glycemic index (GI) of commonly available and consumed fruits and vegetables in Jamaica.…”
Section: Introductionmentioning
confidence: 99%
“…GI indicates the upshot of the content and type of carbohydrates of a food on blood glucose content, while GL estimates how much the food will raise blood glucose level after eating it. GI and GL are considered low for Annona muricata, which agrees with its hypoglycemic potential, [14]. Carbohydrate is the highest macronutrient present into soursop fruit.…”
Section: Nutritional Composition a Total Carbohydratementioning
confidence: 77%